Structural, Optical, Electrical and Photocatalytic Degradation Properties of Cadmium Sulfide Nanopaticles by Sol Gel Methodd - Sankar, M.; Jothibas, M.; Muthuvel, A.; Arun Kumar, B. (Asian Journal of Chemistry, 2020)
Cadmium sulfide (CdS) nanoparticles were synthesized via inexpensive sol gel method at different sintering temperature (350, 400 and 450 °C). The synthesized CdS nanoparticles have been characterized by X-ray diffraction, UV-visible spectroscopy, photoluminescence spectroscopy, scanning electron microscopy, high resolution transmission electron microscopy and Fourier transform infrared spectroscopy. The XRD pattern confirmed the formation of hexagonal Wurtzite structure for all the sintering temperatures. The crystallite size, microstrain and dislocation density have been evaluated using XRD data. SEM and HR-TEM analysis showed morphological transformation with better crystallite and spherical shaped CdS nanoparticles were observed. EDS is also performed to confirm the elemental composition of CdS nanoparticles. FT-IR analysis identified the absorption peaks of the Cd-S extension with moisture content. The UV-visible spectra showed absorption peak in the range of 223-257 nm and optical band gap decrease with increase of sintering temperatures. In addition the synthesized CdS nanoparticles were effectively used to degrade methyl orange dye under sunlight irradiation. The CdS nanoparticles were the potential candidate for optoelectronic applications.